2011
DOI: 10.1038/leu.2011.322
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of ETV6/RUNX1 abrogates PI3K/AKT/mTOR signaling and impairs reconstitution of leukemia in xenografts

Abstract: The ETV6/RUNX1 (E/R) gene fusion is generated by the t(12;21) and found in approximately 25% of childhood B-cell precursor acute lymphoblastic leukemia. In contrast to the overwhelming evidence that E/R is critical for the initiation of leukemia, its relevance for the maintenance of overt disease is less clear. To investigate this issue, we suppressed the endogenous E/R fusion protein with lentivirally transduced short hairpin RNA in the leukemia cell lines REH and AT-2, and found a distinct reduction of proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 43 publications
5
58
1
1
Order By: Relevance
“…A recent report used shRNA-mediated silencing of TEL-AML1 in human leukemic cell lines to demonstrate cell cycle inhibition and impaired engraftment in a xenotransplant mouse model. 22 In line with this observation, we show that silencing TEL-AML1 expression with shRNA targeting the 59 region of TEL, still present in the fusion gene transcript, causes a block in G1/S cell cycle transition in Reh cells (supplemental Figure 8). Moreover, this is accompanied by reduced levels of Tyr705 STAT3 phosphorylation ( Figure 2B).…”
Section: Tel-aml1 Induces Phosphorylation Of Stat3supporting
confidence: 56%
See 2 more Smart Citations
“…A recent report used shRNA-mediated silencing of TEL-AML1 in human leukemic cell lines to demonstrate cell cycle inhibition and impaired engraftment in a xenotransplant mouse model. 22 In line with this observation, we show that silencing TEL-AML1 expression with shRNA targeting the 59 region of TEL, still present in the fusion gene transcript, causes a block in G1/S cell cycle transition in Reh cells (supplemental Figure 8). Moreover, this is accompanied by reduced levels of Tyr705 STAT3 phosphorylation ( Figure 2B).…”
Section: Tel-aml1 Induces Phosphorylation Of Stat3supporting
confidence: 56%
“…18 Analysis of the function of TEL-AML1 in human leukemic cell lines has demonstrated that its continued expression is required for survival, proliferation, and leukemia engraftment. [20][21][22] However, there is only limited information on the signaling pathways deregulated by the fusion in these cells. [22][23][24][25] To address this question, we have used small hairpin (sh)RNA-mediated silencing to demonstrate that TEL-AML1 is responsible for inducing signal transducer and activator of transcription 3 (STAT3) activation in human t(12;21) leukemia cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 mTOR is a serine/threonine kinase, downstream of Akt, that controls cell proliferation and survival. mTOR is the catalytic subunit of two distinct multi-protein complexes, referred to as mTORC1 and mTORC2.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that the protein product of this fusion gene regulates PI3K-AKT-mTOR signaling, as evidenced by the fact that knocking it down with shRNA resulted in reduced AKT and ribosomal protein S6 (rpS6) phosphorylationtwo mTOR-mediated events-while at the same time increasing apoptosis. Furthermore, pharmacologic inhibition of the PI3K-AKT-mTOR pathway with either the PI3K inhibitor LY294002 or the dual PI3K/mTOR inhibitor PI-103 induced apoptosis in ALL cells and sensitized glucocorticoid-resistant leukemia cells to the apoptotic effect of prednisolone [77].…”
Section: Acute Lymphoblastic Leukemia (All)mentioning
confidence: 99%